Strategi Hubungan Masyarakat Kementerian Koperasi dan Usaha Kecil dan Menengah Republik Indonesia Dalam Menyosialisasikan Program Kredit Usaha Rakyat Melalui Media Sosial - Wenny Maya Arlena (Avant Garde, 2020)
The Ministry of of the Republic of Indonesia is a ministry the Government of Indonesia in charge of Koperasi dan Usaha Kecil Menengah. The Ministry of Koperasi dan Usaha Kecil Menengah has 9 (nine) excellent programs, one of which is the Kredit Usaha Rakyat (KUR) program. The Kredit Usaha Rakyat program aims to accelerate the development of the Real Sector and Empowerment of Micro, Small, Medium Enterprises and Cooperatives (UMKMK), and Koperasi to Lembaga Keuangan and Cooperatives to Financial Institutions, as an effort to reduce/reduce poverty and expand employment opportunities, especially for workers small and medium enterprises. Social media contains information that is needed by UMKM to always get the latest information from the central government about UMKM in Indonesia. In socializing this KUR program, the Public Relations Ministry of Cooperatives and SMEs of the Republic of Indonesia socialized it through social media such as Facebook, Twitter and Instagram. But of the three existing social media, Facebook is the focus in socializing the KUR program, because Facebook as social media has many features. The theory used is the POAC theory, using a qualitative descriptive approach and methods through interviews to obtain primary data. The paradigm used is Post-Positivism.